Short stories as an innovative EFL teaching technique to improve Pakistani elementary students’ English vocabulary - Muhammad Safdar Bhatti; Asif Iqbal; Zahida Rafique; Shaista Noreen; Faiqa Tabassum (Journal on English as a Foreign Language, 2022)
Short stories are becoming very popular around the globe. Learning vocabulary, a crucial component of learning a foreign language, is at the heart of teaching a language and is important for language learners. The researchers believe that vocabulary plays a crucial part in learning any language. Therefore, it is crucial to look at the best strategies for enhancing vocabulary learning. With the aim of effectively utilizing short stories to improve vocabulary at the primary level, the current study was created to raise awareness among elementary-level teachers about how they might develop the English vocabulary of their students. The study was experimental with a pretest-posttest design. Sixty students were randomly selected from an elementary school in Bahawalpur, Pakistan. Twenty-five close-ended questions (MCQs) type questions for pre-test and post-test and the English reading assessment survey (ERAS) questionnaire were used to collect data, and the data were analyzed by using SPSS. The results show that most students spoke about three things: the value of short stories in vocabulary learning, their interest in reading short stories, and their approval of using short stories. The study implies that primary school English teachers should use short stories to increase their students' vocabulary.